2003
DOI: 10.1136/ip.9.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Children's bicycle helmet use and injuries in Hillsborough County, Florida before and after helmet legislation

Abstract: The purpose of this research was to explore the changes in children's bicycle helmet use and motor vehicle bicycle related injuries in Hillsborough County, Florida before and after passage of the Florida's bicycle helmet law for children under the age of 16. The results show a significant increase in bicycle helmet use among children, ages 5-13, in the post-law years compared with the pre-law years. Also, there has been a significant decline in the rates of bicycle related motor vehicle injuries among children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…A review of twelve studies from different countries showed that the baseline rates of motorcycle helmet use in different studies range between 4 to 59 percent; however after legislation, this range changed to between 37 to 91 percent (Karkhaneh et al 2006). Researchers have investigated the long-term effects (2 to 11 years) of helmet legislation as compared to short-term ones (less than one year; Cameron et al 1994;Delamater and Patino 2003;Hagel et al 2005;Kanny et al 2001;Leblanc et al 2002;Liller et al 2003) and they have shown that between 10 and 40 percent remained unchanged after the legislation for both motorcyclists and bicyclists.…”
Section: Discussionmentioning
confidence: 95%
“…A review of twelve studies from different countries showed that the baseline rates of motorcycle helmet use in different studies range between 4 to 59 percent; however after legislation, this range changed to between 37 to 91 percent (Karkhaneh et al 2006). Researchers have investigated the long-term effects (2 to 11 years) of helmet legislation as compared to short-term ones (less than one year; Cameron et al 1994;Delamater and Patino 2003;Hagel et al 2005;Kanny et al 2001;Leblanc et al 2002;Liller et al 2003) and they have shown that between 10 and 40 percent remained unchanged after the legislation for both motorcyclists and bicyclists.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies that looked at race as a variable were in predominantly Caucasian populations. Liller et al, in a 2003 study of helmet use in Hillsborough County, FL which is 75% Caucasian, 15% Black, and 18% Hispanic, found that helmet use was highest before and after legislation in the White population [23]. A Maryland study of three counties [24] showed higher helmet use after legislation, but again, in a mainly Caucasian, middle-class population.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies used nonequivalent control groups, 15 27 and 10 were interrupted time series or pre-post observational studies. 16 21 25 26 28-33 While four included studies involved children of school age exclusively, [26][27][28][29] eight included all riding ages. 15 16 21 25 30-33 Among the 12 studies, various cyclist factors were recorded including: age (11), gender (10), location (8), time of day (7), racial characteristics (3), bicycle type (2), backpack use (2), accompaniment (2), and type of road (1) (table 2).…”
Section: Description Of Studiesmentioning
confidence: 99%